Caribbean Near-Shore Coral Reef Benthic Community Response to Changes on Sedimentation Dynamics and Environmental Conditions - Otaño-Cruz, Abimarie; Montañez-Acuña, Alfredo A.; García-Rodríguez, Noelia M.; Díaz-Morales, Dakeishla M.; Benson, Elizabeth; Cuevas, Elvira; Ortiz-Zayas, Jorge; Hernández-Delgado, Edwin A. (Frontiers in Marine Science, 2019)
Coral reefs are facing unprecedented global, regional and local threats that continue to degrade near-shore habitats. Water quality degradation due to unsustainable development practices at coastal watersheds is one of the greatest stressors across multiple spatial scales. The goal of this study was to assess near-shore coral reef benthic community spatio-temporal response to sedimentation patterns, weather, and oceanographic dynamics at Bahía Tamarindo and Punta Soldado in Culebra Island, Puerto Rico. Benthic data were collected across a distance gradient from the shore through high-resolution images at marked belt transects. Environmental data were assessed and contrasted with benthic assemblages using multivariate correlations and multiple linear regression. Coral colony abundance and coral recruit assemblages showed significant variation among seasons, sites and distance zones (PERMANOVA, p<0.01). Species diversity (H’n) increased at both study sites with distance from shore and the most conspicuous coral recruit species were stress-tolerant Porites astreoides, P. porites, and Siderastrea radians. Difference in coral abundance and coral recruits per site had a strong significant negative relationship with sediment characteristics and depth (p<0.05). Near-shore coral reef benthic community structure was significantly different between sites and distance zones from shore, with depth having an important role shaping reef zonation. Changes in benthic community structure were associated with local sediment distribution patterns emerging from human alteration of coastal watersheds and natural events that cause terrigenous sediment deposition and sand resuspension across the reef. Coral cover was significantly lower at zones more exposed to recurrent sedimentation stress (p<0.01). It was also correlated with sediment texture (p=0.006) and terrigenous sediment deposition (p=0.016). Scleractinian coral cover had an inverse relationship with gorgonian and macroalgae cover. In a short-term period, a pattern of increased dominance of encrusting calcareous algae Ramicrusta textilis and invasive sponge Dictyonella funicularis were documented. Changing land use and increased frequency of extreme weather events, as a consequence of global patterns of climate change, may play an important role shaping near-shore coral reefs benthic communities and could threaten the resilience of coastal regions. Therefore, collaborative and trans-disciplinary ecosystem-based management efforts are urgently needed to effectively reduce land-based stressors and foster near-shore coral reef recovery.